RASIONALISASI AGAMA DALAM ARENA POLITIK: DARI PILIHAN IDEOLOGIS KE PERTIMBANGAN RASIONAL - Nurus Shalihin Djamra (Jurnal Dialog, 2016)
This article describes the presence of Islamic party in West Sumatera resulting new dynamics in social and political structure of Minangkabau ethnic. Hence, muslims have boosted the strong and clean democracy because of their participation in politics particularly in 20042009 legislative election. Surprisingly, Islam is not always correlated with political choice. Eventhough the most population in West Sumatera is Islam, but their political choice is not always Islamic parties. The lose of Islam politics (Islamic Parties) in legislative election was the fact. This was seemingly because of shifting paradigm of constituent, from ideological consideration to rational consideration, from identity politics to national politics.